Literature Review: Antidiabetic Activity Of Bay Leaf Infusion (Syzygium Polyanthum) - Anggi Ayu Pratama (Sean Institute, 2024)
Diabetes mellitus (DM) is a group of metabolic disorders associated with elevated blood glucose levels and is predicted to significantly increase in the next 1 or 2 decades. Lowering blood glucose levels (hyperglycemia) can be achieved using the traditional herbal remedy of bay leaf infusion (Syzygium polyanthum). The aim of this review article is to provide a summary of scientific data from several trials on the antidiabetic activity of bay leaf infusion in reducing blood sugar levels. The method in this study is a review article with data collection from April to May using Google Scholar, which resulted in finding 25 relevant journals. The results obtained in this review article show that bay leaf infusion is effective in reducing blood sugar levels in both animal models and patients with diabetes mellitus, with a significant value of p<0.005. This can occur due to the presence of secondary metabolites in bay leaves, such as flavonoids, tannins, saponins, and alkaloids, which can provide antidiabetic effects. In conclusion, there is a significant relationship between the reduction in blood sugar levels and bay leaf infusion due to the secondary metabolites present in bay leaves.